Analysis of optimal humidification temperature for a flue gas thermoelectric generation system with gas humidification. (20th February 2021) - Zhao, Yulong; Yan, Xiangyang; Fan, Yucong; Ge, Minghui; Yue, Like; Wang, Shixue
Abstract: Using thermoelectric generator to recover the condensation latent heat of flue gas for power generation can not only improve the utilization efficiency of fuel but also recover the moisture in the flue gas, making the exhaust cleaner. Based on the heat transfer characteristics of flue gas condensation, a flue gas thermoelectric generation system with gas humidification is constructed, and the mathematical model is established in this paper. By comparing the power generation performance of dry and wet flue gas, it is found that the output power of wet flue gas can reach 2.24 times of dry flue gas, and the moisture recovery rate of flue gas can reach 65.7%. Through gas humidification, the output power of the system can be significantly improved. In addition, the existence of an optimum humidification temperature is found to minimize optimum module area and maximize power output. The mechanism that gives rise to the optimum humidification temperature is discussed, and the condition for the optimal humidification temperature is pointed out. A thermal resistance model of the thermoelectric generator is employed to deduce the relationship between the optimum humidification temperature and initial parameters of the system. It is found that the variation of flue gas and vapor parameters can make the optimal humidification temperature higher than 150 °C. The moisture content of flue gas, heat transfer coefficient of flue gas, and cooling water temperature are the main factors affecting the optimal humidification temperature. The research results have a certain guiding significance for the deep utilization of wet flue gas and clean operation of boilers. Graphical abstract: Image 1 Highlights: The Gas humidification can improve the TEG performance of flue gas. The optimal humidification temperature make TEG have better performance. The existence mechanism of optimal humidification temperature was analyzed. The expression of optimal humidification temperature was deduced. Factors influencing the optimal humidification temperature were discussed.